Intensive measurements of gas, water, and energy exchange between vegetation and troposphere during the MONTES Campaign in a vegetation gradient from short semi-desertic shrublands to tall wet temperate forests in the NW Mediterranean basin - Penuelas, J; Guenther, A; Rapparini, F; Llusia, J; Filella, I; Seco, R; Estiarte, M; Mejia-Chang, M; Ogaya, R; Ibáñez, J; Sardans, J; Castaño, L M; et al. (Atmospheric Environment)
Abstract MONTES (“Woodlands”) was a multidisciplinary international field campaign aimed at measuring energy, water and especially gas exchange between vegetation and atmosphere in a gradient from short semi-desertic shrublands to tall wet temperate forests in NE Spain in the North Western Mediterranean Basin (WMB). The measurements were performed at a semidesertic area (Monegros), at a coastal Meditrerranean shrubland area (Garraf), at a typical Mediterranean holm oak forest area (Prades) and at a wet temperate beech forest (Montseny) during spring (April 2010) under optimal plant physiological conditions in driest-warmest sites and during summer (July 2010) with drought and heat stresses in the driest-warmest sites and optimal conditions in the wettest-coolest site. The objective of this campaign was to study the differences in gas, water and energy exchange occurring at different vegetation coverages and biomasses. Particular attention was devoted to quantitatively understand the exchange of biogenic volatile organic compounds (BVOCs) because of their biological and environmental effects in the WMB. A wide range of instruments (GC-MS, PTR-MS, meteorological sensors, O3 monitors,…) and vertical platforms such as masts, tethered balloons and aircraft were used to characterize the gas, water and energy exchange at increasing footprint areas by measuring vertical profiles. In this paper we provide an overview of the MONTES campaign: the objectives, the characterization of the biomass and gas, water and energy exchange in the 4 sites-areas using satellite data, the estimation of isoprene and monoterpene emissions using MEGAN model, the measurements performed and the first results. The isoprene and monoterpene emission rates estimated with MEGAN and emission factors measured at the foliar level for the dominant species ranged from about 0 to 0.2 mg m-2 h-1 in April. The warmer temperature in July resulted in higher model estimates from about 0 to ca 1.6 mg m-2 h-1 for isoprene and ca. 4.5 mg m-2 h-1 for monoterpenes, depending on the site vegetation and footprint area considered. There were clear daily and seasonal patterns with higher emission rates and mixing ratios at midday and summer relative to early morning and early spring. There was a significant trend in CO2 fixation (from 1 to 10 mg C m-2 d-1), transpiration (from x 1 to 5 kg C m-2 d-1), and sensible and latent heat from the warmest-driest to the coolest-wettest site. The results showed the strong land-cover-specific influence on emissions of BVOCs, gas, energy and water exchange, and therefore demonstrate the potential for feed-back to atmospheric chemistry and climate.
Keywords: aircraft; Boundary Layer; CH4; CO2; Evapotranspiration; green biomass; isoprene; lai; Land Cover; latent heat; masts; MEGAN; Monoterpenes; N2O; NDVI; O3; sensible heat; tethered balloons; Vegetation; vertical profiles; VOCs

Carbon sequestration by Quercus ilex L. and Quercus pubescens Willd. and their contribution to decreasing air temperature in Rome - Gratani, Loretta; Varone, Laura (Urban Ecosystems, 2006)
Carbon sequestration capability by Quercus ilex L and Quercus pubescens Willd., widely distributed in the city of Rome, and their contribution to decreasing air temperature were investigated. Crown volume is the most signiﬁcant (p < 0.01) variable explaining variation of air temperature below the tree crown. Q. pubescens gives a higher contribution to decreasing air temperature during the hottest months, due to its inherent larger crown volume than Q. ilex (252 ± 19 and 533 ± 52 m3 , respectively for the large size). Moreover, our results show the existence of a strong urban carbon dioxide dome with a peak CO2 concentration (on an average 432 ± 37 ppm) at polluted sites, 16% greater than at control sites. Total carbon sequestration is 84 ± 12 and 111 ± 9 Kg year−1 of CO2 for the small Q. ilex and Q. pubescens tree size,respectively, and 151 ± 10 and 185 ± 7 Kg year−1 of CO2 for the large Q. ilex and Q. pubescen tree size, respectively. Q. pubescens, by its higher total photosynthetic leaf surface area (39% higher than Q. ilex) and its higher mean yearly photosynthetic rates (48% higher than Q. ilex) seems to have a greater role than Q. ilex. However, taking into account the leaf longevity (i.e. 12 ± 3 months for Q. ilex and 4 ± 2 months for Q. pubescens), the evergreen species, by its continuous photosynthetic activity, contributes to reduce CO2 throughout the year, and in particular during the winter months, when trafﬁc volume has a pick, than Q. pubescens.
Keywords: Carbon Sequestration; evergreen and Deciduous species; heat island; lai; tree structure